COVD-15. COVIDNEUROONC: A UK MULTI-CENTRE, PROSPECTIVE COHORT STUDY OF THE IMPACT OF THE COVID-19 PANDEMIC ON THE NEURO-ONCOLOGY SERVICE. (9th November 2020) - Fountain, Daniel; Piper, Rory; Poon, Michael; Solomou, Georgios; Brennan, Paul M; Chowdhury, Yasir; Colombo, Francesca; Elmoslemany, Tarek; Ewbank, Frederick; Grundy, Paul; Hasan, Md Tanvir; Hilling, Molly; et al.
Abstract: BACKGROUND: The COVID-19 pandemic has profoundly affected cancer services. Our objective was to determine the effect of the COVID-19 pandemic on decision making and the resulting outcomes for patients with newly diagnosed or recurrent intracranial tumors. METHODS: We performed a multi-centre prospective study of all adult patients discussed in weekly neuro-oncology and skull base MDTs who had a newly diagnosed or recurrent intracranial (excluding pituitary) tumor between 01 April and 31 May 2020. All patients had follow-up data at least 30-days after the index MDT date. Descriptive statistical reporting was used. RESULTS: There were 1357 referrals for newly diagnosed or recurrent intracranial tumors across fifteen neuro-oncology centres. Of centres with all intracranial tumors, a change in initial MDT management was reported in 8.6% of cases (n=104/1210). Decisions to change the MDT management plan reduced over time from a peak of 19% referrals at the start of the study to 0% by the end of the study period. Changes in management were reported in 16% (n=75/466) of cases previously recommended for surgery and 28% of cases previously recommended for chemotherapy (n=20/72). The reported SARS-CoV-2 infection rate was similar in surgical and non-surgical patients (2.6% vs. 2.4%, p >0.9). CONCLUSIONS: Disruption to neuro-oncology services in the UK caused by the COVID-19 pandemic was most marked in the first month, affecting all diagnoses. Patients considered for chemotherapy were most affected. In those recommended surgical treatment this was successfully completed. Longer-term outcome data will evaluate oncological treatments received by these patients and overall survival.